2x-2=-4(x-4)

Simple and best practice solution for 2x-2=-4(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-2=-4(x-4) equation:


Simplifying
2x + -2 = -4(x + -4)

Reorder the terms:
-2 + 2x = -4(x + -4)

Reorder the terms:
-2 + 2x = -4(-4 + x)
-2 + 2x = (-4 * -4 + x * -4)
-2 + 2x = (16 + -4x)

Solving
-2 + 2x = 16 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-2 + 2x + 4x = 16 + -4x + 4x

Combine like terms: 2x + 4x = 6x
-2 + 6x = 16 + -4x + 4x

Combine like terms: -4x + 4x = 0
-2 + 6x = 16 + 0
-2 + 6x = 16

Add '2' to each side of the equation.
-2 + 2 + 6x = 16 + 2

Combine like terms: -2 + 2 = 0
0 + 6x = 16 + 2
6x = 16 + 2

Combine like terms: 16 + 2 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 10-3*x=x+4 | | -9=6+5v | | 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 | | 12x-20=7x+20 | | f(20)=0.05x+3 | | 9c-4=26-c | | 50=5(3m-2) | | -15(-B)= | | 1/4=2/x | | -42=4t | | d/5-3=-4 | | 7+3t=5t-1 | | -0.6k-1+0.5k=3 | | g/10=10 | | 4x+-5y=-12 | | 276/6 | | 6c-3c+2d-4d= | | 2m+4=m-10 | | 0=x^2-20x+100 | | 5h/3=15 | | bxA=c | | 13x-6=4(3x+2)-2 | | 150,000,000/1.18=1.18N/1.18 | | y=42x+15 | | -33=2(v-6)-5v | | a+a.32=-325 | | (x+2)*(x+2)=14 | | -7x=6+3 | | 7/10=n/6 | | 3(m-2)=2(m+1)-3 |

Equations solver categories